RECOGNITION OF NATURAL CAPITAL IN FINANCIAL REPORTING IN THE CONTEXT OF THE SOCIO-ECONOMIC PARADIGM: PRACTICE OF THE REPUBLIC OF MOLDOVA AND INTERNATIONAL EXPERIENCE - Irina GOLOCHALOVA; Maria COJOCARU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the context of ensuring sustainable development, the activity of a business unit has come to be seen as a three-component system designed to provide reliable information about the contribution of business to the social and environmental segments of the economy. This trend led to the transition to the socio-economic paradigm of financial reporting, which predetermines its revolutionary transformations, one of which is finding ways to recognize natural capital (NC) and disclose information about its impact on the value of the business as a whole. This article puts forward and proves the hypotheses, which leads to the following conclusion: the recognition of NC as an element of financial reporting is an imperative of the socio-economic reporting paradigm. This study was conducted on the basis of general scientific and special methods: systematic approach, collection and comparison, analysis, synthesis, modeling, study of special literature. The justification of the hypotheses is carried out according to the following scheme: the current state of natural capital of the Republic of Moldova is assessed; the national accounting and financial reporting system is characterized in the context of the requirements of the socio-economic paradigm; methodological aspects of the recognition of natural capital as an element of financial reporting are analyzed; an algorithm and arguments of the NC recognition model based on the provisions of IFRS are proposed.